Study of Correlation between Iron Deficiency Anemia and Serum Lipid Profile in a Tertiary Care Center - Bataju, Mahima; Bhattarai, Binita; Niraula, Apeksha; Priyadarshinee, Anamika; Gautam, Santosh (Nepalese Medical Journal, 2021)
Introduction: Looking at the health status of our country Nepal, iron deficiency anemia fits rightly in our socioeconomic status and dyslipidemia is the rising one along with being more highlighted these days. Some studies show an association between iron deficiency anemia and dyslipidemia but the data are controversial. Therefore, this study is aimed to find the relationship between iron deficiency anemia and serum lipid profile in the Nepalese context. Materials and Methods: A cross-sectional study was conducted in KIST Medical College and Teaching Hospital from June 2019 to August 2020. 76 Iron deficiency anemia and 75 age and sex-matched healthy control were investigated for any possible changes in serum lipid profile: triglyceride, low-density lipoprotein, high-density lipoprotein, and total cholesterol. Results: The mean triglyceride in case and control was 92.96 mg/dl and 99.87 mg/dl respectively. The difference between these two groups was statistically significant (p=<0.001). Moreover, serum total cholesterol level in the case (138.82 mg/dl) was significantly lower than the control (146.67 mg/dl). The mean high-density lipoprotein was almost the same in anemic and non-anemic groups, p=<0.001. While the mean low-density lipoprotein in the iron-deficiency anemia group was significantly lower than the control group (p=<0.001). Conclusions: In this study, the values of the lipid profile parameters: triglyceride, low-density lipoprotein, high-density lipoprotein, and total cholesterol in cases were found to be lower than those in the controls.